Visceral Adipose Tissue Indices Independently Correlated with Obstructive Sleep Apnea in Patients with Type 2 Diabetes - Caiyu Zheng; Xuanling Zheng; Xiaoyan Lin; Jiawen Ye; Ziqing Xu; Huixian Hu; Wengui Wang; Caoxin Huang; Jianqing Tian; Changqin Liu (Journal of Diabetes Research)
Aims. We aimed to explore whether visceral adiposity indices were significantly associated with obstructive sleep apnea (OSA) in type 2 diabetes (T2DM) patients. Methods. 100 patients with T2DM who underwent overnight polysomnography were analyzed in this study. Anthropometric data, lipid profiles, and glycemic parameters were recorded. Body fat percentage (BFP) and visceral adipose tissue area (VAT area) were collected from a whole body scan using dual-energy X-ray absorptiometry (DXA). Multivariate logistic regression analysis was performed to explore the associations of AHI with BFP, VAT area, and CVAI. Results. The prevalence rate of OSA was 80%, and the mean (±SD) of age was 47.0±13.6 years. Apnea-hypopnea index (AHI) was significantly and positively associated with either VAT area (r=0.433, p≤0.001) or Chinese visceral adiposity index (CVAI) (r=0.355, p≤0.001) but not for BFP (r=0.107, p=0.294). Multivariate logistic regression analyses showed that VAT area and CVAI were significantly associated with increased risk of OSA, and the adjusted ORs were (95% CI) 1.025 (1.003-1.047, p=0.023) and 1.018 (1.002-1.034, p=0.030), respectively. However, there was no significant association between BFP and increased risk of OSA. Conclusions. VAT area and CVAI were independent risk factors of OSA in the patients with T2DM.